O cinema ressignificando a educação ambiental através de uma prática interdisciplinar - Oliveira, Malize Lourdes de (2015)
This study recommends using the use of technological resources as a teaching tool/learning of Environmental Education, through the production and dissemination of short films produced in the school environment. Thus, the present research, qualitative feature, aims to produce films (short films) on environmental education, in an interdisciplinary environment. For this, we propose the adoption of a methodology you press the action research which prioritizes the construction of alternative proposals for improving the school routine. It is considered that the objective was achieved fairly well, as three short films were produced, two fictions - "The history of R 5"; and "Before out today delivery" and Music Video - "For the world to renew." This production participated students and adult education teachers in a fully interdisciplinary environment. It follows that environmental education work in this environment, from the resources similar to those used in film, is motivating for both students and for teachers.